Perceived Stress, Sexual and Marital Satisfaction among Married Healthcare Workers in Nigeria - Matthew Idowu Olatubi; Olamide Olayinka; Olufemi Oyebanji Oyediran; Grace Oluwaranti Ademuyiwa; Taiwo Omotayo Dosunmu (Department of Nursing, Faculty of Medicine, Diponegoro University, 2022)
Background: Marital and sexual satisfaction are essential for conjugal bliss and harmony. However, stress in the workplace can influence sexual and marital satisfaction of couples. There is dearth of information about level of sexual and marital satisfaction among healthcare workers in Nigeria, as well as the connections between stress, sexual and marital satisfaction among healthcare workers. Purpose: This study assessed inter-relationship between perceived stress, sexual and marital satisfaction among married healthcare workers.Methods: This descriptive cross-sectional study adopted a quantitative approach among 150 consented healthcare workers recruited using a simple random sampling technique. Instruments for data collection included the Perceived Stress Scale, Enrich Marital Satisfaction questionnaire and Pinney Sexual Satisfaction Inventory. The Pearson correlation was used to ascertain relationships and linear regression was done to predict influence of one variable on the other.Results: Perceived level of stress of the healthcare workers was low [16.9(0.001)] and mean sexual satisfaction (SS) was poor [78.93(23.68)]. Also, 49.3% were found to be the dissatisfied maritally. Perceived stress showed a positive correlation with marital satisfaction (MS) (r=0.48, p<0.01). However, stress negatively correlated with participants’ SS with partners (r=-0.51, p<0.01). Similarly, general SS positively correlated with MS (r=0.32, p<0.01). Predictors of MS included perceived stress (β=0.614, p=0.01), age differences with spouse (β=0.30, p=0.01), number of children (β=-0.24, p=0.01), and family type (β=-0.21, p=0.05).Conclusion: Only half of the participants in this study are maritally satisfied. Marital satisfaction increases with sexual satisfaction. Stress is correlated with reduced sexual satisfaction of the participant, and as number of children increases, marital satisfaction reduces. Couples should be encouraged to give birth to moderate number of children to improve marital satisfaction.